Characteristics of the soil arbuscular mycorrhizal fungal community along succession stages in tropical forest and its driving factors - Mai, Siwei; Mao, Han; Jiang, Yamin; Huang, Ting; Yang, Qiu; Xing, Guitong; Wang, Xiaofang; Yang, Huai; Liu, Wenjie (Frontiers in Environmental Science, 2023)
Arbuscular mycorrhizal fungi play an important role in mediating plant-soil interactions across succession stages. However, AMF community dynamics which about the change of community composition and member activity remain unclear. To complete the gap knowledge about microbial community dynamics during restoration succession, soil AMF community composition was studied within a tropical forest ecosystem in the Ganshiling nature reserve using high throughput sequencing methods. The results revealed that soil AMF communities characteristics about speices diversity, species composition and microbial correlation network showed significant differences between shrubland (SC) and secondary forest ecosystems, but the same differences were not found between 40-year recovery secondary forest (SF40) and 60-year recovery secondary forest (SF60). Plant community dynamics were the key factor for regulating soil AMF communities among succession stages. An important biotic factor explaining variance in AMF community composition was root biomass. The correlation network analysis showed that although the nodes were similar among succession stages, the complexity of networks was significant higher in SF40 than in SC and SF60, suggesting that AMF communities were more active in SF40, which verified the hypothesis of intermediate disturbance hypothesis. This study provides new insights into AMF community dynamics and their driving factors across succession stages, as well as expanding knowledge of the ecological value of AMF for tropical forest restoration processes.